Current status of salt reduction in bread and bakery products – A review. (November 2016) - Silow, Christoph; Axel, Claudia; Zannini, Emanuele; Arendt, Elke K.
Abstract: Cardiovascular disease, including hypertension, is the leading cause of preventable death worldwide. Sodium chloride (NaCl) associated with its excessive consumption is linked to hypertension while the global dietary NaCl intake has increased extensively. Thus, limitations on sodium (Na) consumption were recommended by the WHO and further international health agencies (<2 g Na/day). Bread and other cereal products contribute about 30% to the daily intake of sodium in the western human diet. Although it may sound simple, salt reduction in foods is not as straight forward since salt impacts the processability during the production and the quality characteristics of the final bakery products. To achieve the final reduction goals long-term strategies and reformulation of recipes are required. Numerous different techniques have been proposed to reduce the sodium chloride content. Other approaches include salt replacers or enhancers. These are summarized with special attention given to recent developments over the last 5 years. One of the promising strategies to reduce salt has been the addition of sourdough to bakery goods. Sourdough can counteract some of the negative impacts salt reduction has on bread (e.g., flavour, shelf life) improving the overall quality. The present review describes and assesses the impact of NaCl reduction on a range of bakery products, including dough characteristics, sensory properties and shelf-life. It further outlines the progress that has been made in salt reduction and indicates existing problems in the bakery sector. Highlights: Bread is a major contributor to sodium intake. Health organisations aim for further salt reduction in food products. Sourdough is a useful functional ingredient for salt-reduced breads. Other strategies include taste enhancers, Na-replacers and bitter flavours.